P467 Circulating CD8 α4β7+ and CD8b7+ memory T cells as early biomarkers of clinical response to vedolizumab in ulcerative colitis. (25th January 2019) - Gonzalez-Vivo, M; Lund Tiirikainen, M K; de Jesús Gi, C; Ruiz-Romeu, E; Sans, L; Canillas, L; Andreu, M; Santamaria-Babí, L F; Marquez, L
Abstract: Background: Vedolizumab (VDZ) is a humanised monoclonal antibody targeting the α4β7 integrin us in ulcerative colitis (UC). So far, no biomarker of response to VDZ has been identified. AIM: To assess whether circulating CD4+ and CD8+ α4β7+/ α4β7- memory T lymphocytes are molecular markers of response to VDZ treatment in patients with UC. Methods: Prospective study, 15 patients with active UC (Ulcerative Colitis Disease Activity Index (UCDAI) >3, Mayo endoscopic subscore >1, faecal calprotectin >250 μg/g) and with prior failure to anti-TNFα therapy, starting treatment with VDZ ( 300 mg iv, standard induction regime). Peripheral blood sample obtained just before first dose of VDZ, purification of circulating memory T cells (CD45RO+) and simultaneous analysis of CD CD4+ and CD8+ limphocitic subpopulations (α4β7+/−, HLA-DR+/−, CD25+/−, IL23R+/−, CCR9+/−, IL17A+/−, IL-23R+/−, IL-9+/−, β7 +/−) by flow citometry. Clinical response and remission (UCDAI clínic) and faecal calprotectin levels were evaluated at Weeks 6 and 14. Results: Eight females, age 46 ± 16 years extent (Montreal E1: 2 patients, E2: 8 patients, and E3: 5 patients), 7 severe colitis (UCDAI > 9). At Week 6: 9 patients were in clinical response, 7 patients were in clinical remission and 8 patients had faecal calprotectin levels <250 μg/g. At Week 14 : 10 patients remained in clinical response, 8 were in clinical remission and 10 patients had faecal calprotectin levels <250 μg/g. Patients with clinical response, clinical remission and faecal calprotectin levels < 250 μg/g at Week 6; and clinical remission and faecal calprotectin levels < 250 μg/g at Week 14, presented an absolute account of CD8 α4β7+ and CD8b7+ memory T cells at baseline significantly higher when compared with patients with no VDZ response (Table 1). No differences were identified according to the severity of the flare or the extent of the disease. No statistically significant differences were identified in the other lymphocyte subpopulations included in the study. Conclusions: The absolute account of CD8 α4β7+ and CD8b7+ memory T cells before starting VDZ treatment could be early biomarkers of clinical response, allowing to select a subset of patients that are more likely to respond to VDZ.